MEMBACA AL-MUTANABBI DAN HUBUNGANNYA DENGAN TIGA PENGUASA ABBASIYAH (Analisis Semiotik) - Walidin, Muhammad; Suratno, Chamamah (Universitas Muhammadiyah Surakarta, 2007)
A research entitled âReading al-Mutanabbi> and Its relation to the Three Caliphsof Abbasid: A Semiotic Analysisâ aims to describe semiotically a relation betweenal-Mutanabbi> and the three Caliphs of Abbasid. The relation shows the role andsuccess of al-Mutanabbi>> as an outstanding Arabian poet. The research results inshowing the relation between al-Mutanabbi> and the three caliphs of Abbasid determinedby some factors, namely the character of al-Mutanabbi> , i.e. loyal, stiff,helpful, smart, polite, and arrogant; the characteristics of the poetries, i.e. diplomatic,contradictive, hyperbola, pars pro toto; and the pattern of the relation created,i.e. patronage, friendship, and mutual relation. Although the character is animportant element to maintain the quality of the relation, the special characteristicof the al-Mutanabbi>âs poetries is the most significant element to create the goodrelation with the three caliphs. In addition, the characteristics of al-Mutanabbi> âspoetries are needed by the caliphs to increase their image in front of their publicand enemies.